Zingiber Officinale Effect on Immune Event Against Newcastle Disease Virus with Productive Performance of Broilers - Firas Hussein AL-bawi1 , Raed Salih Rabee (Indian Journal of Forensic Medicine & Toxicology, 2020)
Study the effects of different concentration of Zingiber officinale or called ginger (GG)on productive performance, blood biochemistry as White blood cells (WBC), Red blood cells (RBC), Packed cell volume (PCV), haemoglobin (Hb) and immune status against Newcastle disease (ND) virus of broilers. These experiment used (180) broilers chicks of one day age type Hubbard . All chickens vaccinated against ND on day 7 the chicks, which divided randomly into (4) groups and each group of (45) chicks. The study showed the effects of different concentration of (GG) given in 2g/kg, 4g/kg and 6g/kg with feed Groups of T0, T1, T2, T3, T0 as control and T1, T2, T3, as treatment. Parameters of body weight, weight gain, feed consumption and feed conversion . Statistical significant (P < 0.05) increased value of body weight, weight gain, feed consumption and feed conversion was observed in T3, then T2 . A non-significant value was observed in T1 (2g/kg of GG) as compared to T0 (control). Significant (P < 0.05) increases in the WBC, RBC, PCV and Hb. The ginger additives groups showed significant (P < 0.05) increases in hemagglutination inhibition (HI) titer against ND virus. In conclusion, 4 - 6 g/kg of GG additives to broiler chicks feed, enhanced growth performance, enhance WBC, RBC, PCV, Hb and showed significant (P < 0.05) increases in hemagglutination inhibition (HI) titers against ND virus, while group T1 had less significant effects compared to the other groups.